Har engler skjegg? Folk og engler i Skandinavia på 1500- og 1600-tallet - Amundsen, Arne Bugge (Tidsskrift for kulturforskning, 2025)
The article examines in what contexts and in what ways encounters with angels have occurred in 16th and 17th century Scandinavia. Three Lutheran theologians’ views on angels are presented: Peder Palladius, Jesper Brochmand and Jens Jersin. In Lutheran theology and preaching, angels were positively referred to as part of daily piety, but direct encounters with angels were problematic because they challenged the idea that the Bible represented the full and final divine revelation. Several such direct encounters with angels in Denmark, Sweden and Norway are then analysed. The perspective is that angels and encounters with angels were part of the ‘cultural repertoire’. The angels could express support for the Lutheran ideals of piety, but they could also protest against sin, bad years and war.